SANTRI ENTREPRENEUR ECOSYSTEM BASED ON BUSINESS MODEL CANVAS AT AL-MUJTAHIDDIN ISLAMIC BOARDING SCHOOL - Hamzah, Zeze Zakaria; Anwar, Syaiful; Hamdani, Muchamad (LPPM Univ. Ibn Khaldun Bogor, 2024)
Background: Entrepreneurial motivation among students is not yet optimal. Not to mention the rapid development of the times, technology changes so quickly. If explored, the role of students in entrepreneurship will certainly increase. Objective: Increase students' understanding of how to preach in the digital world. Method: Carrying out entrepreneurship training, capacity building, visits to MSMEs, BMC training, video editing training and uploading on YouTube. Results: Implementation of collaborative activities between STIE Dewantara Lecturers, Students, Soniaco 2000 Printing, and Work Garis Design.. Conclusion: The students can preach and upload on YouTube